Nutritional strategies in the management of Alzheimer\'s disease: systematic review and meta-analysis - Muñoz Fernandez, Shirley Steffany (2016)
Alzheimer\'s disease (AD) is one of the main causes of dependency and disability in the elderly population. A number of investigations have been seeking its prevention and/or management. In this context, it is important to highlight the role of modifiable risk factors, such as nutrition. This study aims to conduct a systematic review and subsequent meta-analysis, to assess the effect of food and/or nutrients for the management of AD at different stages. This work was steered based on the Cochrane Handbook for systematic reviews of interventions and the PRISMA Statement. Electronic databases were searched up to 2014, in Portuguese, English or Spanish. Relevant publications were identified by title and abstract using key search terms referring to Alzheimer\'s disease, nutrition interventions and type of study. Trials\' risk of bias was appraised by applying the Cochrane\'s tool for assessing risk of bias. The main outcome measures comprise neuropsychological tests such as MMSE, ADCS-ADL, NPI and CDR-sob, biomarkers and brain imaging. Pairwise meta-analyses were performed in a random-effect model by estimating the weighted mean differences between treatment and placebo groups, with 95% confidence intervals for outcome measures by treatment. Network meta-analysis and the ranking probability of treatment for each nutrition intervention were undertaken on cognitive outcome. The strength and quality of evidence were rated according to the GRADE approach. From the whole research, 182 studies met the systematic review\'s purpose. Thirty-five clinical trials complied with eligibility criteria and risk of bias assessment. Included studies utilized: antioxidants, B-vitamin complex, carbohydrates, lipids, omega-3 fatty acids, polymeric formulas, polypeptide and vitamin D. Estimates treatment effects from pairwise meta-analyses show a significant positive effect from the supplementation with proline-rich polypeptide (WMD 12.00 [95% CI 10.20, 13.80] P < 0.00001) and B-vitamin complex (WMD 0.44 [95% CI 0.09, 0.79] P = 0.01) on cognitive function measured by the MMSE. Remaining nutrients supplementation did not show any significant effect on functional, behavioral, global performance, biomarkers or brain imaging outcomes. Isolated nutrient supplementations show no convincing evidence of providing a significant benefit on clinical manifestations or neuropathology of AD. As a treatment strategy, nutrients did not show any effect when delivered individually, probably due to their synergistic work on brain function at different domains. Nevertheless, nutrients represent a potential preventive approach and an adjuvant treatment for patients with AD at earlier stages.